Customers' Islamic ethical behavior: the case of Malaysian Islamic banks. Issue 3 (14th August 2017) - Zakiah, Farah; Al-Aidaros, Al-Hasan
Abstract : Purpose: The purpose of this paper is to determine the framework of customers' Islamic ethical behavior in Islamic banks in Malaysia. Design/methodology/approach: This paper used a quantitative approach based on Maqasid Shariah (objectives of Islamic law) and by running exploratory factor analysis. A survey questionnaire was created. The data of 530 respondents were collected from the customers of Islamic banks located in Malaysia. Findings: The findings revealed that the theoretical framework consists of four main constructs: Islamic ethical behavior, religious obligation, reputation and profit and investment, in which all constructs are complying with Maqasid Shariah and three (i.e. Islamic ethical behavior, religious obligation and reputation) consist of two components for each construct. Research limitations/implications: There are two limitations that require further acknowledgements. First, the study population only focused on Islamic banks' customers. Second, this research highlighted only Malaysia and Malaysian citizens. Originality/value: The paper contributes to the literature on Islamic ethical behavior in Southeast Asian economy. Unlike other Islamic ethical studies where the writing is mainly theoretical in nature, this study used an empirical method to reveal what should constitute for the framework of customers' Islamic ethical behavior which is based on Maqasid Shariah .